“It’s where I buy lunch or anything that I want to buy”: a participatory photo elicitation study on adolescents’ experience of food choice and environment in Kisumu, Kenya - Elisa Gobbo; Alice Achieng Ojwang; Kristi Sidney Annerstedt; Joseph Ochieng Amoke; Loyce Joyce Anyango; Sibylle Herzig van Wees; Donvan Nunda; Edward Ouko; Esther Oruko; Helle Mølsted Alvesson (Journal of Health, Population and Nutrition, 2026)
Abstract Background In Kenya, adolescents face a rapidly changing nutritional landscape, a growing triple burden of nutrition, and a rising risk of non-communicable diseases. Behaviors that begin in adolescence can influence lifelong dietary patterns and future disease risk. Yet, there is limited understanding of contextually grounded, adolescent-centered experiences of their food environments and food choice in the African Region. This study aims to address this gap by exploring how young adolescents attending school in an informal settlement in Kisumu, Kenya, experience and visualize their local food environment. Methods This is a qualitative participatory study using the visual methods of photo elicitation and social foodscape mapping. Participants took photos of their food environment and then participated in group-based discussions and mapping with researchers. The participants were recruited using convenience sampling from grade 7 until information power was reached. Eighteen adolescents participated (9 females, 9 males, ages 12–13 years). Nine have access to a phone at home. 157 unique images and 17 map drawings were created. Data were analyzed using Drew & Guillemin’s three-stage methodology and an abductive reflexive thematic analysis to interpret both images and narratives. Results The analysis generated three main themes: (1) food choices are shaped by convenience and familiarity, yet the adolescents express an interest in items beyond the familiar, (2) adolescents mostly receive food from adults but are beginning to make some independent choices, and (3) adolescents value the social dimensions of food, yet they navigate different forms of belonging across family and peer contexts. Overall, adult routines and provisions remain central, but adolescents value moments of autonomy and express curiosity for more processed and peer-valued foods. Conclusions These young adolescents in Kisumu are navigating an early transition point shaped by financial constraints, physical accessibility, and adult-led routines. However, they also express pride in independent choice and interest in greater influence. This signals they are developing volitional autonomy within their social and environmental constraints. These findings position early adolescence as a critical window for intervention to enhance adolescents’ capacity to negotiate healthy food choices and influence lifelong dietary patterns.